Physical fitness of elite female Rugby Union players - Hene, N. M.; Bassett, S. H.; Andrews, B. S. (African Journal for Physical, Health Education, Recreation and Dance, 2011)
Rugby union is a contact sport in which players require high levels of physical fitness, which is a composite of aerobic and anaerobic endurance, muscle strength and power, speed, agility and body composition. The aim of this study was to assess the physical fitness characteristics of elite female rugby union players. Thirty two elite female rugby players who were members of the South African Rugby Union High Performance Squad were assessed during the pre-season. The players were sub-divided into two positional categories consisting of 17 forwards and 15 backs. The players underwent a comprehensive physical fitness testing (height, body mass and sum of seven skinfolds, sit-and-reach, vertical jump, 10m and 40m speed, 1 RM bench press, pull-ups, one minute push-ups and multi-stage shuttle run test). Analysis of variance was used to examine the difference between forwards and back-line players with regards to physical fitness. There were statistical differences (p < 0.01) between positional groups, as forward players had a greater body mass, sum of skinfolds and body fat percentage than back-line players. In terms of explosive leg power, speed, muscular endurance, back-line players demonstrated superior performances. In contrast, no significant differences were detected between forward and back-line players in terms of flexibility, upper body strength (1 RM bench press and pull-ups) and estimated maximal aerobic power. These findings provide the coaches with a good understanding of the physical fitness of elite female rugby union players.